Maltrato físico y su incidencia en la salud mental de una adolescente de 16 años en el cantón Pueblo Viejo - Contreras Cevallos, Jodye Malú (2023)
This research is based on the physical abuse suffered by a 16-year-old adolescent girl from Puebloviejo, which had repercussions on her mental health, causing depression and low self-esteem in the patient. The methodology used for this case study is qualitative, through which the variables: physical abuse and mental health were investigated; following the research line of prevention, diagnosis, evaluation and psychotherapeutic treatment; and the research subline of individual and/or group psychotherapies. The techniques used were focused on cognitive behavioral therapy, two psychometric tests were performed: Rosenberg self-esteem scale and Beck depression test for adolescents, which resulted in low self-esteem and moderate depression; in turn, tools that favored the diagnosis of the patient were used, tools such as: clinical history, clinical observation, and semi-structured interview.